PENGARUH PAJAK, EXCHAGE RATE, DAN KEPEMILIKAN ASINGTERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN TRANSFER PRICING - PUSPITA AKHADYA, DWI; ARIEFTIARA, DIANWICAKSIH (Jurnal Akuntansi AKUNESA, 2018)
The Company?s conducts transfer pricing with the aim of minimizing the company?s tax. Transfer pricing occurs in multinational companies influenced by related party transactions. Several factors that influence transfer pricing in addition to taxes including exchange rates and foreign ownership. This research aims to determine the effect of tax, exchange rate, and foreign ownership of company to transfer pricing. This research used multinational companies that listed on the Indonesia Stock Exchange (IDX) periode 2013-2016 as a sampel research with a total sampel of 124 companies. The dependent variable in this study is transfer pricingand taxes, exchange rates, and foreign ownership as independent variables. Technique of data analysis in this research uses the SPSS23 and used logistic regression analysis. This result shows that tax and foreign ownership has an effect of the company?s decision to transfer pricing.Besides that, exchange rate has no effect to the company?s decision to transfer pricing.Keywords: Exchange Rate, Foreign Ownership, Tax and Transfer Pricing